Rudolf J. Vonka, vertaler of verminker? Hoe het spel met de omvang van teksten leidde tot populariteit van Nederlandstalige literatuur in Tsjechië in het interbellum - Engelbrecht, Wilken (Acta Neerlandica, 2023)
Rudolf J. Vonka (1877–1964) was one of the most important Czech translators of Dutch literature in the interwar period. He is best known as the translator of novels by the then internationally renowned Flemish writer Felix Timmermans. His translations were very successful, received positive reviews and were reprinted, sometimes long after the Second World War. However, the Dutch translator and netherlandist Olga Krijtová (1931–2013) discovered that Vonka had largely adapted the translated texts, which is a serious offence according to Czech translatological standards. The contribution discusses Vonka’s position and work as a translator and possible motives for his approach. Finally, it shows why Vonka can after all be considered an important contributor to the spread of Dutchlanguage literature in the Czech Republic.